Xylarenones C−E from an Endophytic Fungus Isolated from Alibertia macrophylla - Oliveira, Camila Martins de (2011)
Xylarenones C-E (2-4), three new eremophilane sesquiterpenes, have been isolated from solid substrate cultures of a Camarops-like endophytic fungus isolated from Alibertia macrophylla. The structures were elucidated by analysis of spectroscopic data. Compounds were evaluated in subtilisin and pepsin protease assays, and compound 2 showed potent inhibitory activity against both proteases.